Financial market prediction by artificial intelligent techniques - Kaung, Mon Thaw. (2010)
Strategies and tools have been applied on financial market by the investors, to optimize the returns and minimize the risk involved in trading. Mathematical, statistical, and numerous techniques are applied on the analysis of financial market. Technical analysis techniques which use charts and indicators have been popular among the professional traders for a long time. Nowadays, with the advances in computer softwares (programs), prediction softwares using artificial intelligent are the latest tools available to apply on financial market. Study of technical analysis techniques and artificial intelligent techniques are involved in the project scope. Analysis of the effectiveness and accuracy of these techniques are carried out through virtual trading. The experiment results are shown in the portfolio. In contrast, profit margin of 6% is achieved from the virtual trading.